What's the Story? "Credible" Narrative in the Evaluation of Arts and Culture. Issue 6 (2nd November 2019) - Meyrick, Julian; Barnett, Tully; Robinson, Heather; Russell, Matt
Abstract: Narratives are an important tool in organizational theory, but we need a better analysis of their affordances to be fit for the purposes of the arts and cultural sector. This article considers the relation between the concept of narrative as a theoretical object and its use in the practical evaluation of cultural organisations and events. It considers the historical development of narrative as a tool of persuasive speaking and looks at the tension between narrative and numerical information. It concludes by considering how a revised, principles-based approach to "credible" narrative in reporting can be applied to the cultural sector through a proposed Charter of Cultural Reporting. Thus, it advocates refining the use of narrative to communicate forms of value that would be otherwise lost to reductive quantitative indicators and cliched language. Researchers interested in questions of value in arts and culture should attend to ways that narrative can function to promote a meaningful evaluative environment that suits the needs of stakeholders and creates a voice for those with an interest in cultural outcomes.